VALIDITAS BAHAN AJAR BERBENTUK E-BOOKLET SUBTOPIK PROSES REPLIKASI VIRUS BERBASIS PROBLEM BASED LEARNING PADA SMA KELAS X - Andriani, Dewi; Noorhidayati, Noorhidayati; Halang, Bunda (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Twenty-first century learning demands that teachers be more creative, innovative, and collaborative, with the ability to integrate digital technology into instructional models to foster students' 6C skills: character, citizenship, critical thinking, creativity, collaboration, and communication. One alternative learning resource aligned with both 21st-century competencies and the independent learning curriculum is the electronic booklet (e-booklet). This study aims to evaluate the suitability, feasibility, and readability of teaching materials in the form of an e-booklet on the subtopic of the virus replication process, designed based on the Problem-Based Learning (PBL) model for Grade X high school students. The research employed a Research and Development (R&D) approach using the 4D model by Thiagarajan et al. (1974), which in this study was implemented up to the limited dissemination stage in a test school and through publication. Data were collected using evaluation instruments for content suitability, technical feasibility, and readability. Participants included three experts (two Biology Education lecturers from FKIP ULM and one teacher from SMAN 13 Banjarmasin) and twelve Grade XI students from SMAN 13 Banjarmasin. The results showed that the e-booklet was rated "very suitable" (score: 4.60), indicating alignment with learning objectives, language, format, and media; "very feasible" (score: 4.82), reflecting technical viability as a teaching material; and "very good" for readability (score: 4.78), showing it is easy for students to understand. These findings suggest that the developed e-booklet is a highly effective alternative to conventional teaching materials.